Early left ventricular diastolic function and disease severity in congenital diaphragmatic hernia - Cantone, Giulia Vanina; Bhattacharya, Abhijit; Healy, David; Levinkopf, Dana; Massolo, Anna Claudia; Pugnaloni, Flaminia; Vento, Giovanni; Heuchan, Anne Marie; Kipfmüller, Florian; Patel, Neil (Pediatric research, 2025)
Congenital diaphragmatic hernia (CDH) remains a major cause of neonatal mortality and morbidity. Early systolic left ventricular (LV) dysfunction is well described in CDH, while diastolic impairment remains unexplored. This study aimed to investigate the feasibility LV diastolic function assessment and to evaluate its relationship with clinical severity.
Gesehen am 12.01.2026